The African peer review mechanism – how far so far? - Sven Grimm; Prince Mashele (Deutsches Institut für Entwicklungspolitik (DIE), 2006)
Concern with governance has become a prominent topic in Africa. With the African Review Mechanism (APRM), African leaders have addressed a taboo in post-independence Africa. The Organisation for African Unity's (OAU) emphasis on the sacrosanct principle of non-interference and territorial integrity has been used by most African governments to abdicate their responsibility to protect human rights as well as to avoid accountability for bad governance. The OAU successor organisation, the African Union (AU), aspires at introducing a different political culture. The most direct governance framework, embraced by the AU, is the New Partnership for Africa's Development (NEPAD). Predating the AU by one year, NEPAD does not only deal with socio-economic issues, it also addresses political governance. A special feature of NEPAD is the APRM, which sets out the governance preconditions for development. All countries acceding to the APRM are, therefore, expected to improve their governance in line with a set of identified preconditions. Previous assessments have shown some overall improvements in political representation throughout Africa, while shortcomings in the areas of corruption and effectiveness of institutions prevail. However, a number of countries have signed up to the APRM that face questions on the credibility of their political will to conduct a thorough analysis. Thus far, very little is known about how the peer review process actually unfolds at a country level. Ghana and Rwanda have completed the first full-cycle peer review mechanism in Africa, and their respective reports are expected to be published in the first half of 2006. Kenya is about to follow. Other countries, namely Mauritius, South Africa and Nigeria, are progressing on their reports and have seen public debate about the reviewing process. Processes in Ghana and Rwanda – precedents for other countries to follow – have unrolled in different forms, especially with regard to civil society participation. Some critical comments of the reports are expected: they are likely to highlight Ghana's bloated government and Rwanda's lack of governance capacity. A crucial aspect will be the government's reactions to recommendations of the reviews. Donors should align to the recommendations to foster African capacities. At the same time, support for civil society institutions seems necessary in the light of the two almost completed review processes.
Keywords: 330